FDTD Seismic Simulation of Moving Tracked Vehicle - Ketcharn, Stephen A.; Moran, Mark L.; Greenfield, Roy J. (2000)
This paper describes the utility of a large finite-difference time domain (FDTD) simulation of seismic wave propagation from a spatially and time varying source that generically represents a moving tracked vehicle. The focus is the computational approach and requirements for the long- duration simulation, the geologic model, the moving vehicle force algorithm, the resulting particle velocity wave fields, and example applications of the data. The 8th order FDTD simulation consisted of parallel computations based upon a domain decomposition strategy. The computations were performed using a Sun workstation cluster at the U.S. Army Engineer Research and Development Center's Cold Regions Research and Engineering Laboratory (ERDC-CRREL). Our use of such a cluster was necessary because of the spatial extent of the model and the duration of the simulated event; the model dimension is roughly 210 m by 286 m by 80 m (deep) with 1.6-m node spacing, and the event duration is 24.6 s with time steps of 180 microseconds. The event duration reflects the time required for the vehicle to traverse the model surface at an average speed close to 45 km/h. Three-component particle-velocity wave-field histories over this duration were stored by the simulation for later processing. Models of this extent and duration are on the order of the expected range of coverage for battlefield systems such as Raptor or the Future Combat System sensor system. As a consequence, resulting simulation data can be used for system development in a manner similar to field data. See also ADM201471, Papers from the Meeting of the MSS Specialty Group on Battlefield Acoustic and Seismic Sensing, Magnetic and Electric Field Sensors (2001) Held in Applied Physics Lab, Johns Hopkins Univ, Laurel, MD on 24-26 Oct 2001. Volume 2 (Also includes 1999 and 2000 Meetings), The original document contains color images.